The Effect of Slow Deep Breathing Exercise on Headache and Vital Sign in Hypertension Patients - Yanti Anggraini Aritonang (Jurnal Keperawatan Padjadjaran, 2020)
Prevalence hypertension was estimated 1.13 billion people in the world and 2.027.006 (20.0%) people in DKI Jakarta. Headache was a common symptom related to high blood pressure levels. Slow Deep Breathing Exercise was non pharmacological therapy to reduce consumption of oxygen, metabolism, frequency of respiration, frequency of heart, muscle tension and blood pressure. This research was a pre-experimental one group pre-test post-test design and the respondents performed slow deep breathing exercise fourth time in one day during fourth days. Before and after intervention, the respondents measured vital sign and assessed headache scale with subjective and objective (a numerical scale 1-10). The number of samples in this study were 30 respondents who were selected by probability random sampling and were included in the inclusion and exclusion criteria. Research time December 2019-January 2020 at UKI General Hospital and Cawang District Health Center, East Jakarta. The results showed differences before and after Slow Deep Breathing Exercise on the decrease in headache scale with p-value = 0.000 and on the decrease in blood pressure with p-value = 0.000 and on the pulse rate of 0.014, breathing frequency 0.008 and temperature 0.000 (<0.001). Before intervension, patients feels headache on 7 scale and after intervention, respondents felt no headache on 0 scale. Conclusion are Slow Deep Breathing Exercise have an effect to reduce headache scale and vital sign for four days . The suggestion for the nurse teachs Slow Deep Breathing Exercise to hypertensive patients so that patients can do these exercises at home as an independent exercise.